KEPENTINGAN GUINEA-BISSAU MEMBAJAK KAPAL M/V VIRGINIA G MILIK PANAMA - Jefri Januardi; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This paper describes aim to Guinea-Bissau pirating the M/V Virginia belongs to Panama. The Virginia G is an oil tanker registered under the flag of the Republic of Panama. The Virginia G is fully owned by Penn Lilac Trading S.A, a Panamanian company. On the 21 August 2009, the Virginia G supplied the gas oil to fishing vessel in Economic Exclusive Zone (EEZ) Guinea-Bissau, when the refueling was about to commence, two unidentified, Zodiac-type speedboats approached the Virginia G.According to Liberalism perspectives on International Relations by Robert Gilpin about The State and The Multinationals. Formulation of all arguments, facts, and theoretical framework on this research is guided by qualitative explanation methods. Technique in this research is through by the study of library. Data which is gotten and collected through the journal books and then from internet has related to the problems.Finally, the reason of Guinea-Bissau pirating the M/V Virginia G belongs to Panama because of the importance to protect domestic companies. Guinea-Bissau is a country with a very slow economic growth and are included in the category of the lowest per capita incomes in the world. Besides, Economic growth in Guinea-Bissau is dominated by the oil company in the country which is actually the son of a Portuguese company that Galp energia. Galp energia cooperation with Guinea-Bissau because it is incorporated in the organization of the Portuguese speaking countries, namely the Community of Portuguese Speaking Countries (CPLP).Keyword : M/V Virginia G, Guinea-Bissau, EEZ